2023
DOI: 10.3390/w15030609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotational Speed on Pressure Pulsation Characteristics of Variable-Speed Pump Turbine Unit in Turbine Mode

Abstract: The pumped storage power station plays a vital role in modern power systems, where the key component is the pump turbine. Variable-speed operation can improve the operating efficiency of the pump turbine and increase the operating efficiency under turbine operating conditions and the automatic frequency regulation capability under pump operating conditions, thus obtaining higher efficiency and better stability. However, its operation characteristics are different from many conventional pumped storage units, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…For the internal and external pressure balance pipe structure, the current domestic and international research mainly focuses on the flow pattern in the high-pressure chamber and the influence of setting the internal pressure balance pipe [26][27][28]. Lin [29] analysed the axial force characteristics of pump turbine before and after setting internal pressure balance pipe.…”
Section: Brief Description Of Internal and External Pressure Pipe Str...mentioning
confidence: 99%
“…For the internal and external pressure balance pipe structure, the current domestic and international research mainly focuses on the flow pattern in the high-pressure chamber and the influence of setting the internal pressure balance pipe [26][27][28]. Lin [29] analysed the axial force characteristics of pump turbine before and after setting internal pressure balance pipe.…”
Section: Brief Description Of Internal and External Pressure Pipe Str...mentioning
confidence: 99%
“…He Wang et al [8] proposed an optimization step in variable-speed operation based on the model of a VSPSU. In terms of operational stability, Linmin Shang et al [9] revealed that the stability of VSPSUs decreases with the increase of speed in turbine mode. Giovanna Cavazzini et al [10] illustrated the effect of the S-Shape zone in turbine mode and the hump zone in pump mode on power regulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, most PSH plants are only capable of regulating their power production output in turbine mode [4], while pumps are only able to run at full capacity. Furthermore, the conventional fixed speed pumped storage units (FSU) cannot meet the requirements of fast and accurate regulation when frequency fluctuation occurs [5,6], especially in the grids with high proportion of intermittent renewable energy [7]. With variable speed drives, (1) the operation efficiency and stability of the turbine can be improved, (2) the pump input power can be regulated, and (3) the unit can respond to the power fluctuation of the power grid in milliseconds by flywheel effect [8].…”
Section: Introductionmentioning
confidence: 99%